Heat Transfer and Fluid Flow in Naturally Ventilated Greenhouses - Elashmawy, M.; Al-Rashed, A. A. A. A.; Kolsi, L.; Badawy, I.; Ali, N. B.; Ali, S. S. (Engineering, Technology & Applied Science Research, 2017)
In this paper, heat transfer and fluid flow in naturally ventilated greenhouses are studied numerically for tow configuration according to the number and positions of the opening. The equations governing the phenomenon are developed using the stream function-vorticity formalism and solved using the finite volume method. The aim of the study is to investigate how buoyancy forces influence airflow and temperature patterns inside the greenhouse. Rayleigh number is the main parameter which changes from 103 to 106 and Prandtl number is fixed at Pr=0.71. Results are reported in terms of stream function, isotherms and average Nusselt number. It is found that the flow structure is sensitive to the value of Rayleigh number and the number of openings. Also, that using asymmetric opening positions improve the natural ventilation and facilitate the occurrence of buoyancy induced upward cross-airflow inside the greenhouse.